Strategi Menurunkan Turnover Intention Akuntan Pada Kantor Jasa Akuntansi Pekanbaru Tahun 2021 - Nicholas Renaldo; Rizaldi Putra; Suhardjo; Suyono; Ienne Yoseria Putri (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
To retain the best talent in order to stay in the Accounting Services Office (ASO), good human resource management is an important part to compete with competitors through its accountants, especially in Pekanbaru city. The purpose of this study was to analyze the effect of Green Human Resources Management (GHRM) on turnover intention. The data collection method used in this study was through a questionnaire that was distributed to 122 accountants at KJA in Pekanbaru City which would be tested for the feasibility of the questionnaire before further analysis. The data analysis method used path analysis and sensitivity tests. The results of this study indicate that green training and development, green compensation, and green performance assessment each have a positive and significant effect on green organizational commitment. The variables of green training and development, green compensation, green performance assessment, and green organizational commitment each have a negative and significant effect on turnover intention. Sensitivity testing also showed consistent results. Green performance assessment has the biggest direct and indirect effect on turnover intention. Organizations pay attention to objectivity in evaluating employee performance so as not to lose the best employees in the organization. Organizations must also pay attention to green organizational commitment because it can mediate the three exogenous variables on turnover intention. Organizations must be able to maintain the commitment that has been embedded in the minds of employees so that they want to remain in the organization. Keywords: turnover intention, GHRM, path analysis, sensitivity tests, ASO